Glucose transfer from dolichol monophosphate glucose: the product formed with endogenous microsomal acceptor - Behrens, Nicolás H. (1971)
The product formed by incubation of dolichol monophosphate glucose with liver microsomes was studied. It is insoluble in most solvents, but is soluble in a chloroform-methanol mixture with a high content of water. Treatment with ammonia gave rise to the formation of a water soluble, negatively charged compound of molecular weight 3550. The negative charge could be removed by treatment with phosphatase. Acid hydrolysis of the original compound led to the liberation of an uncharged, water-soluble compound (molecular weight 3550). Acetolysis of the latter gave rise to the formation of a series of products, which appeared to be oligosaccharides when chromatographed on paper or silica plates. The original substance behaved like a polyprenol pyrophosphate when chromatographed on DEAE-cellulose. Molecular weight measurements of the deoxycholate inclusion compound gave a value of 14,300, while dolichol monophosphate glucose under the same conditions gave 11,300. It is tentatively suggested that the compound is dolichol joined through a phosphate or pyrophosphate bridge to an oligosaccharide containing about 20 monosaccharide residues.